ANALYSIS OF HISTORICAL BUILDINGS NGAWEN TEMPLE IN MAGELANG - Sariningtias, Rizki; Indriani, Reza; Solihati, Anisa; Kamila, Alya; Pamungkas, Megita Dwi (MaPan : Jurnal Matematika dan Pembelajaran, 2020)
The analysis of historical buildings Ngawen Temple has a purpose of knowing the history of Ngawen Temple and knowing the approach to the Ngawen Temple's geometry. This research type is descriptive research with a qualitative approach. The subject of this research is the historical building of Ngawen Temple. The data collection techniques used in this research are interviews and documentation (observation) directly. The interview was done with the temple officers around the building, and the documentation was taken directly. The data analysis technique is done by analyzing the buildings related to the geometry, such as the building's shape on the Ngawen Temple. The results of this study were obtained; namely, Ngawen Temple set in Buddhism. The Ngawen Temple complex consists of 5 (five) temples that line the parallel from north to south. Temple building facing the east. From the south of Ngawen Temple I, II, III, IV, and V, each temple plans the square. One of Ngawen Temple's uniqueness is the existence of 4 lion statues in every corner of temple II and Candi IV. Another uniqueness is the temple's architecture, found in a lion's statue that supports the four sides of the temple building reconstructed from the five buildings. The lion statue's carved style resembles the lion symbol of Singapore's country and serves the rainwater that comes out through the statue's mouth. The Ngawen Temple's shape resembles the cuboid's geometry, the rectangular pyramidal frustum, and the rectangular pyramid.